“Other” Discriminations: Salary and Labour Conditions for Teacher Training Colleges Participation in Extraordinary Budget : Discriminaciones “otras”: análisis de las condiciones salariales y laborales en las escuelas normales indígenas para participar en el presupuesto extraordinario (Papeles, 2022)
This research reveals how the regulatory frameworks and financial policies in Mexican Higher Education make up exclusion and neglect scenarios for the Indigenous teacher training colleges. The analysis shows discrepancies between what is expected of Normal Schools and the conditions under which they perform. We illustrate how the frameworks and logics of resource distribution have an unequal impact on the development of substantive functions.
Keywords: discrimination; education budget; college of education; working conditions of teachers; educational policy